2018
DOI: 10.1021/acs.jpclett.8b02151
|View full text |Cite
|
Sign up to set email alerts
|

Role of H Transfer in the Gas-Phase Sulfidation Process of MoO3: A Quantum Molecular Dynamics Study

Abstract: Layered transition metal dichalcogenide (TMDC) materials have received great attention because of their remarkable electronic, optical, and chemical properties. Among typical TMDC family members, monolayer MoS2 has been considered a next-generation semiconducting material, primarily due to a higher carrier mobility and larger band gap. The key enabler to bring such a promising MoS2 layer into mass production is chemical vapor deposition (CVD). During CVD synthesis, gas-phase sulfidation of MoO3 is a key elemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
4
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 48 publications
2
4
0
Order By: Relevance
“…Reaction steps in Scheme are based on the primary reaction pathway observed during our QMD simulations, whereas different reaction pathways may exist depending on the system temperatures, system pressure, and initial precursors used. According to our previous work, MoS 2 can be formed with different pathways when using MoO 3 and H 2 S reactants . However, the reaction pathways, derived by unbiased QMD simulations in this work, provide a new physical insight into the accelerated reduction and sulfurization steps (Figure ) with the level of quantum mechanical accuracy, which may support the observation in the experimental synthesis of MoS 2 layers using the MoO 3 reactants and H 2 S/H 2 mixture.…”
supporting
confidence: 82%
See 1 more Smart Citation
“…Reaction steps in Scheme are based on the primary reaction pathway observed during our QMD simulations, whereas different reaction pathways may exist depending on the system temperatures, system pressure, and initial precursors used. According to our previous work, MoS 2 can be formed with different pathways when using MoO 3 and H 2 S reactants . However, the reaction pathways, derived by unbiased QMD simulations in this work, provide a new physical insight into the accelerated reduction and sulfurization steps (Figure ) with the level of quantum mechanical accuracy, which may support the observation in the experimental synthesis of MoS 2 layers using the MoO 3 reactants and H 2 S/H 2 mixture.…”
supporting
confidence: 82%
“…According to our previous work, MoS 2 can be formed with different pathways when using MoO 3 and H 2 S reactants. 43 However, the reaction pathways, derived by unbiased QMD simulations in this work, provide a new physical insight into the accelerated reduction and sulfurization steps (Figure 3) with the level of quantum mechanical accuracy, which may support the observation in the experimental synthesis of MoS 2 layers using the MoO 3 reactants and H 2 S/H 2 mixture.…”
supporting
confidence: 71%
“…12 In the case of hydrogen sulfide, adjacent molybdenum oxyhydride clusters resulting from surface interactions with hydrogen sulfides condense into a reduced surface whose interactions with the reduced hydrogen sulfide lead to the formation of Mo−S bonds. 13 Experimental and computational studies of gas phase elemental sulfur have shown the allotrope composition of sulfur in the gas-phase to contain S 2 −S 8 under typical powder vaporization growth conditions. 14−16 Using this information, we previously reported the thermodynamics of the sulfurization by analyzing the gas-phase reaction between molybdenum compounds and the sulfur allotropes present in the growth chamber under typical growth conditions.…”
Section: ■ Introductionmentioning
confidence: 99%
“…One of the critical parameters is growth temperature. Growth temperatures ranging from approximately 800 to 1275 K have been reported. ,, In contrast, the mechanism of sulfurization by hydrogen sulfide has been more widely studied both computationally and experimentally. In addition, the mechanisms of sulfurization of a molybdenum trioxide surface by elemental disulfur and by hydrogen sulfide have recently been investigated from a computational standpoint. In the case of disulfur as the precursor, oxygen molecules leave the surface to form oxysulfide gas-phase molecules that subsequently react with a reduced surface to form Mo–S bonds .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation